PENERAPAN KONSEP EKOWISATA BERBASIS MASYARAKAT DENGAN MEMPROMOSIKAN KEARIFAN LOKAL MENUJU PARIWISATA YANG BERKELANJUTAN DI TANA TORAJA - Thoban, Maryam A.A.; Warlina, Lia (Universitas Komputer Indonesia (UNIKOM), 2017)
ABSTRAK Tana Toraja has a very diverse tourism potential, not only about cultural but beautiful landscape too. However, the tourism potential is not managed properly. Local wisdom which still preserved is potency for local communities to manage and maintain it independently. Community Based Ecotourism concept is a development concept which approriate to the condition of society and the environent in Tana Toraja, so as toinvolve the local community becomes a way to meet the needs oof economic, and social while ensuring sustainability of culuturan and natural resources. This study aims to provide a concept of tourism development with the application of community based ecotourism concept by local wisdom promoting in Tana Toraja. Data were collected by in-dept interview and observation to the manager of tourist atracction, community of handicraft and stakeholders. The method of analysis is descriptive analysis. The results from this study indicate that the involvement of local communities as managers of tourist atracctions, homestay providers, transportation service providers, and local guide are still lacking. However, Tana Toraja has the local wisdom resources which can be promoted to become a educational material for tourists. Kata Kunci: Tourism, Community Based Ecotourism, Local Wisdom, Sustainable Tourism, Tana Toraja